Regards sur le nouveau droit de la famille au Canada anglais et au Québec - Guay-Archambault, Denyse (Les Cahiers de droit, 1981)
The English origin of the law in the Common law jurisdictions in Canada makes it mandatory to study common law and English statutory law. It is through those that we can follow the development of a family property law in English Canada. Starting from an individualistic view of the spouses' property, we shall witness the emergence of the idea of « family assets » which has been « enshrined » in recent legislation. The law of Québec has evolved differently. Though of Trench origin, it has not kept as near its mother-country as its neighbour's has done with English law. Turthermore, due to its civilian character, its principles of private law are to be found in the Civil Code. This favours a different approach. That is why we will generally confine our study to those rules which are to be found in the Code civil du Bas-Canada and to the newly adopted Code civil du Québec. We will see what has become of the original community of property and compare the present law of Québec with recent legislation in English Canada.